Retrospective review of Duke men`s basketball eye care: annual screenings and traumatic injuries - Wisely, C. E.; Legault, G.; Kim, T. (The Physician and Sportsmedicine, 2021)
Objectives 1) To assess the utility of performing eye screenings for healthy basketball players. 2) To describe the traumatic injuries sustained by competitive college basketball players.